2021
DOI: 10.1177/03611981211029648
|View full text |Cite
|
Sign up to set email alerts
|

High Friction Surface Treatment Deterioration Analysis and Characteristics Study

Abstract: High friction surface treatment (HFST) is used to improve friction on curved roadways, especially on curves that have a history of wet pavement crashes. Observations on the long-term performance monitoring of HFST sections at the National Center for Asphalt Technology (NCAT) Test Track showed friction (skid number, SN) dropped significantly at the end of service life of HFST, creating unsafe driving conditions. There is no clear, observed friction deterioration trend to predict the friction drop when using fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The subjectivity challenge can be addressed using 3D pavement-scanning technologies that can be used objectively to assess aggregate loss and other distresses based on texture characteristics. The observed relationship between highlighted texture parameters and DFT friction shows that texture parameters (including traditional mean profile depth, ridge to valley depth, and HFST topography-based parameters, such as average height, angularity, and density) are promising for detecting poor (low) HFST friction performance and can potentially predict low friction concerns on HFST sites (3,11). Thus, state transportation agencies can leverage their 3D pavement-scanning technologies (that state DOTs have already used to collect 3D pavement data) to cost-effectively and regularly monitor HFST friction deterioration.…”
Section: Module 4: Performance Measurement Technologies and Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The subjectivity challenge can be addressed using 3D pavement-scanning technologies that can be used objectively to assess aggregate loss and other distresses based on texture characteristics. The observed relationship between highlighted texture parameters and DFT friction shows that texture parameters (including traditional mean profile depth, ridge to valley depth, and HFST topography-based parameters, such as average height, angularity, and density) are promising for detecting poor (low) HFST friction performance and can potentially predict low friction concerns on HFST sites (3,11). Thus, state transportation agencies can leverage their 3D pavement-scanning technologies (that state DOTs have already used to collect 3D pavement data) to cost-effectively and regularly monitor HFST friction deterioration.…”
Section: Module 4: Performance Measurement Technologies and Proceduresmentioning
confidence: 99%
“…The authors have performed studies at the NCAT test track to study the characteristics of HFST aggregate loss and its relationship with friction. The authors (a) identified HFST aggregate loss characteristics (based on appearance and surface texture), including the color contrast between HFST surfaces and their background pavement colors and changes in 3D macrotexture ( 3 ), (b) characterized HFST aggregate loss using quantitative parameters, such as aggregate loss areas derived from color contrast and 3D surface macrotexture parameters derived from topographical properties (such as aggregate height, shape, and density [ 11 ]), and (c) revealed a strong correlation between DFT friction and aggregate loss areas, and, also, a strong correlation between friction (DFT60) and 3D macrotexture parameters. The authors’ study provides sufficient evidence to conclude that HFST friction deterioration is largely controlled by HFST aggregate loss and change in macrotexture.…”
Section: Proposed Comprehensive Hfst Life-cycle Management Frameworkmentioning
confidence: 99%
See 3 more Smart Citations